Clinical researchRandomized double blind prospective trial of active management of the third stage of labor - Tharakan, Tessie; Jha, Jayanti (Archives of Medical Science, 2008)
Introduction: To determine if timing and mode of administration of prophylactic oxytocin influences duration of the third stage of labor, amount of blood loss, and incidence of third stage complications. Material and methods: A randomized double-blind prospective trial in singleton vaginal deliveries comparing oxytocin intravenous injection after infant delivery versus infusion after placental delivery. Vials of medication oxytocin/saline were prepared by the hospital pharmacy. Results were analyzed after study completion, using the Student’s t test. Results: Ninety-nine patients were recruited; 64 completed the study, 32 in each group. The study group received oxytocin after second stage. Drop out occurred due to rapid labor, and due to cesarean deliveries. The two groups were comparable for age, parity, gestational age, and birth weight. Mean (± SD) subjectively estimated blood loss (EBL) showed a statistically significant difference (315.53±91.97 vs. 384.38±116.7, p=0.01). Hematocrit drop and duration of third stage showed a trend to be less in the study group. No cases or controls had retained placenta, hypotension, cardiac arrhythmias, or post partum hemorrhage. Conclusions: Intravenous injection of oxytocin after the second stage is safe and effective compared with common practice of oxytocin infusion after placental delivery. Future larger studies may show larger benefits.